PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR KECAMATAN KENDIT KABUPATEN SITUBONDO - Dafid Nur Afandi; Eddy Basuki; Hari Susanto (ACTON, 2018)
Competence is the authority, ability or capability of a person to carry out a task or job in accordance with the occupied position. The Work Environment is a social, psychological, and physical life in an organization that affects the employees to do their job. The Job Satisfaction is the level of pleasure that a person feels for his role or work in an organization. However, in reality there are still some employees who have not been competent in carrying out their work in the Kendit District Office Situbondo Regency. Therefore, this study aims to determine the Effect of Competence and Work Environment on Employees Satisfaction in the Kendit District Office Of Situbondo District. The respondents in this study are 32 people. The sampling technique used saturated sampling technique which means that the entire population is used as a sample. Data analysis in this study used classical assumption test, t test, f test, multiple linear regression analysis and coefficient of determination with the help of SPSS version 23 for Windows as the software assistance. The results shows that the competency and work environment variables has a positive and significant influence on employee job satisfaction.